Human upper extremity motor cortex activity shows distinct oscillatory signatures for stereotyped arm and leg movements - Starkweather, Clara Kwon; Morrison, Melanie A.; Yaroshinsky, Maria; Louie, Kenneth; Balakid, Jannine; Presbrey, Kara; Starr, Philip A.; Wang, Doris D. (Frontiers in Human Neuroscience, 2023)
Stepping and arm swing are stereotyped movements that require coordination across multiple muscle groups. It is not known whether the encoding of these stereotyped movements in the human primary motor cortex is confined to the limbs' respective somatotopy. We recorded subdural electrocorticography activities from the hand/arm area in the primary motor cortex of 6 subjects undergoing deep brain stimulation surgery for essential tremor and Parkinson's disease who performed stepping (all patients) and arm swing (n = 3 patients) tasks. We show stepping related low frequency oscillations over the arm area. Furthermore, we show that this oscillatory activity is separable, both in frequency and spatial domains, from gamma band activity changes that occur during arm swing. Our study contributes to the growing body of evidence that lower extremity movement may be more broadly represented in the motor cortex, and suggest that it may represent a way to coordinate stereotyped movements across the upper and lower extremities.